Concurrent Validity of the International Family Quality of Life Survey. Issue 2 (2nd April 2016) - Samuel, Preethy S.; Pociask, Fredrick D.; DiZazzo-Miller, Rosanne; Carrellas, Ann; LeRoy, Barbara W.
ABSTRACT: The measurement of the social construct of Family Quality of Life (FQOL) is a parsimonious alternative to the current approach of measuring familial outcomes using a battery of tools related to individual-level outcomes. The purpose of this study was to examine the internal consistency and concurrent validity of the International FQOL Survey (FQOLS-2006), using cross-sectional data collected from 65 family caregivers of children with developmental disabilities. It shows a moderate correlation between the total FQOL scores of the FQOLS-2006 and the Beach Center's FQOL scale. The validity of five FQOLS-2006 domains was supported by the correlations between conceptually related domains.